MODEL PEMBELAJARAN LANGSUNG TERHADAP KETERAMPILAN VOKASIONAL SISWA TUNADAKSA DI SMALB–D - Annisa Anatasiya, Sella (Jurnal Pendidikan Khusus, 2018)
ABSTRACT Vocational skills needs for disable teenagers, so they can have ability to survive in society as well as will not depend on others. In this research, skills obtained was culinary skills especially producing banana and cassava chips. Direct learning was applied in this study by giving structural procedural learning conducted through stages. This research aimed to examine the effect of direct learning model for vocational skills of students at SMADB-D YPAC Surabaya. This research used a quantitative approach with pre-experimental research by One Group Pretest Posttest Design. The experiment was conducted by 8 meetings consisting 1 pretest, 6 treatments and 1 posttest and was participated by 6 students of SMALB-D YPAC Surabaya. The data analysis revealed that the average score for the pre-test was 47.84 and the post-test was 69.75. In conclusion, Zcount was 2.05 compared to the crisis value 5%, so Ztabel was 1.96. It indicated that Zcount is higher than Ztable (Zh > Zt), meaning that Ho was rejected and Ha was accepted. Thus, it showed that direct learning influence vocational skill of disable student at SMALB-D YPAC Surabaya. Keyword: Direct learning, Vocational.